Teatro e autoridade digital: planejamento de conteúdo e sua importância nos ambientes de ensino - ALMEIDA, Igor Martins Sousa Bacelar (2024)
To begin the discussions, arguments and considerations presented in this work, a brief introduction is given to the reasons that made it possible and gave rise to the construction and development of this research. This Course Conclusion Paper presents a bibliographical survey of the Theater Research Seminars (SPT) and, for discussion, some notes on communication and the lack of active presence in digital media, making connections with the work of digital space researchers such as Martha Gabriel, Rafael Terra, Henry Jenkins and Marshal McLuhan who, through their work, guide the way I developed the construction of this research. In the development section, five parts are presented in which a timeline of fifteen years of the SPT is shown and how each period is or isn't present in digital media, so this work places within academia the debate about what is being done with the knowledge generated during the event, where the historical records of the editions are going and whether the target audience is participating and being reached effectively in this process. And finally, the conclusion of this TCC is presented with the necessary considerations to be made about the subject discussed here.